EFEKTIVITAS TEKNOLOGI - Maria Widyarini (Center for Economic Studies Universitas Katolik Parahyangan, 2001)
Productivity and quality are the keys of success for business. One of alternatives to entrance productivity and quality is adopting new technology. With the new technology, firms can operate their activities effectively and efficiently. The technology effectivity can be determined as the succesfulness of technology in order to increase human welfare that expressed in product, process and system. This paper will explain briefly about the technology effectivity and the relationship between technology effectivity and productivity of the firms.